THE NEURONAL ANTIINFLAMMATORY EFFECTS OF APELIN-13 - Doğantekin, Akif; Doğantekin, Esin; Gözel, Nevzat (Mümin POLAT, 2023)
Objective: Apelin, a peptide with growth factor characteristic, is expressed in many cells and acts by binding to the APJ receptor. Apelin mRNA was detected in the central nervous system (CNS), macrophages and many peripheral tissues. According to recent studies, apelin protects neurons from hypoxia and glutamate-mediated excitotoxicity and can protect cells from oxidative stres (stress) (OS) damage by stimulating catalase activity. Pituitary and neurodegenerative diseases are associated with progressive neuronal loss in the CNS. Neuroinflammation and OS-induced cell damage, caused by microglia and astrocytes activation, have an important role in the pathogenesis and prognosis of these diseases. The aim of this study is to investigate the effects of apelin-13 molecule on the development of inflammation and OS caused by bacterial endotoxin in an invitro astrocyte cell culture medium. Methods: The effect of apelin -13 on cell viability changes in lipopolysaccharide (LPS) induced astrocyte inflammation was analyzed by enzymatic MTT test. The anti-inflammatory effects were determined by qRT-PCR and ELISA analysis at the level of TNF-?, IL-1?, IL-6 and mRNA transcription and protein. The effects of apelin on endotoxin mediated OS and possible DNA damage, lipid peroxidation, and nitric oxide (NO) production were evaluated by ELISA method. Results: In our study, LPS application to astrocytes caused inflammation and a significant decrease in inflammation was found with apelin treatment. Conclusion: The results obtained from this study reveal the antiinflammatory, antiapoptotic and antioxidant effects of apelin, that have widely expressed receptors and role in the development of immune response on the development of neuroinflammation and oxidative cell damage.
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi